2010
DOI: 10.1111/j.1751-1097.2010.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Bioluminescence, Bioelectromagnetics and Function

Abstract: The biological functions of light emission in bacterial bioluminescence are not always obvious, especially if the bacteria are in a free-living mode. Experimental evidence suggests that light emission confers benefit to the bacteria themselves such as through photoreactivation and involves as much as 20% of cell energy metabolism. A theoretical model shows if the effect is mediated solely by light then cells should be luminescent at both high and low cell densities, therefore raising doubt over the photoreacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…5 B1) keep the cells close together, miming a higher cell density, and this could possibly induce a quorum-sensing response leading to higher bioluminescence intensity. This is in agreement with previous hypotheses from Pooley [48].…”
Section: Resultssupporting
confidence: 94%
“…5 B1) keep the cells close together, miming a higher cell density, and this could possibly induce a quorum-sensing response leading to higher bioluminescence intensity. This is in agreement with previous hypotheses from Pooley [48].…”
Section: Resultssupporting
confidence: 94%
“…Thus, millimeter ⁄ submillimeter waves might be involved in a cooperative response within the quorum [31]. Taking into consideration these observations, implementation of electromagnetic fields as quorum-quenching agent has been proposed [32]. But it has been also suggested that expression of genes involved in bacterial luminescence might be controlled by other factors, for example SOS regulon [25].…”
Section: Evaluation Of Luxb Gene Expressionmentioning
confidence: 99%
“…and perception of low-frequency ionic currents [1] and optical wavelength photons [2][3][4], it looks reasonable to ask whether cells or organisms have also developed an ability to use radiofrequency and microwave electromagnetic fields for communication/signaling purposes as several authors proposed [5][6][7][8][9]. Fields of the frequencies of 3 MHz up to approx.…”
mentioning
confidence: 99%